Contemporary integrative taxonomy for sexually deprived protists: A case study of Trachelomonas (Euglenaceae) from western Ukraine. Issue 1 (10th April 2020) - Žerdoner Čalasan, Anže; Kretschmann, Juliane; Gottschling, Marc
Abstract: As many other protist groups, euglenophytes are prone to false identification based solely on morphology because of a limited amount of morphological features and cryptic speciation. One of the supposedly completely asexual groups within the freshwater phototrophic representatives of euglenophytes is Trachelomonas, capable of forming an inorganic shell around its cell (i.e., the lorica). The International Code of Nomenclature for algae, fungi, and plants regulates the taxonomy not only of flowering plants, but explicitly also of phototrophic protists, and provides powerful tools to resolve various taxonomic challenges. To exemplify some of the problems and potential solutions, a number of Trachelomonas strains were collected from the muddy, lake‐rich region of Dobrostany and cultivated under stable laboratory conditions. Being a type locality of 58 unclarified Trachelomonas names, this region in western Ukraine is of great taxonomic importance. Based on light and electron microscopy, and on RAxML and MrBayes phylogenetics using multiple loci and a representative taxon sample, a detailed description of investigated strains and their systematic placement is provided. Morphologically, the strains differed slightly but consistently in minute characters such as size, lorica shape and ornamentation. The presently most comprehensive molecular tree of the Euglenaceae indicated to the existence of at least five different species present in the newly investigated samples, although they were collected from localities in very close vicinity to each other and at the same date. Based on morphological comparisons with type illustrations of species validly described 100 or more years ago, biological material was used to epitypify three names of Trachelomonas, eternally linking morphology with reliable genetic information. This taxonomic application is one of the powerful methods to clarify ambiguous scientific names, which has particular importance in character‐poor protists such as the euglenophytes.